Comparative analysis of two models for the optical response of a thin slab: a film of finite thickness versus a surface current sheet. Issue 8 (8th February 2023) - Chen, Shuo; Liu, Haotuo; Wu, Biyuan; Wu, Xiaohu; Fu, Ceji
Abstract : Two calculation models (a finite thickness film and a surface current sheet) for the optical response of a thin slab are compared and investigated, which can be explained by the Fabry–Perot and Berreman resonances. Abstract : An accurate description of the electromagnetic properties of materials is fundamental to optical and electric devices. As a current research hotspot, thin slabs generally are modeled as a film of finite thickness with a dielectric function. However, inspired by two-dimensional materials, thin slabs can be regarded as surface current sheets with conductivity. Due to the convenience of the latter in simplifying the calculations, it becomes increasingly significant to determine the equivalent conditions of the two models. In this work, we compare the differences between the thin film and surface current models in calculating the transmissivity, reflectivity, and absorptivity of a SiC film. For normal incidence, the difference between the calculations of the two models is only non-negligible when the thickness is large (500 nm), because of the invalidation of surface current models and the excitation of Fabry–Perot resonance. In particular, we derive analytical formulas for the relative error in transmittance versus phase difference, which can be used to predict the difference between the two models as a function of film thickness. For oblique incidence, the two models have significant differences in the vicinity of epsilon-near-zero (ENZ) frequency. The excitation of the Berreman leaky mode in a thin film model causes a narrow blank absorption peak close to the ENZ frequency. However, we found that the surface current model is unable to form this resonance mode and further demonstrate it theoretically. In addition, it is found that the two models are equivalent in the case of a transverse electric wave even though the incidence is oblique. This work can enhance the awareness of the light–matter interaction and open unprecedented avenues for designing ultrathin optical devices.